2016
DOI: 10.30659/ijibe.1.2.161-170
|View full text |Cite
|
Sign up to set email alerts
|

Fund Management Strategy in Baznas Zakat (Amil Zakat National Agency) East Java

Abstract: Poor people in the world remains a global problem. Previous studies have been widely using various perspectives related to aspects of fundamental and macroeconomic. However, research that focuses on methods to manage zakat institutions still do not exist. Especially on zakat management institutions in Indonesia. Countries with a Muslim majority population in the world. This study used a qualitative approach through multiple cases study aimed to determine the zakat fund management strategies at the National Zak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…No previous research is found in this case, while zakat fundraising is an important issue in some Muslim countries. Most of previous studies only discussed zakat agency management (Owoyemi, 2020;Widiastuti, Wahyuningsih, & Indrawan, 2016), accountability and transparency of zakat agency (Nikmatuniayah, Marliyati, & A, 2017) in a single country. To contribute to fill this gap, this paper compares incentive zakat agency mechanism between Indonesia and Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…No previous research is found in this case, while zakat fundraising is an important issue in some Muslim countries. Most of previous studies only discussed zakat agency management (Owoyemi, 2020;Widiastuti, Wahyuningsih, & Indrawan, 2016), accountability and transparency of zakat agency (Nikmatuniayah, Marliyati, & A, 2017) in a single country. To contribute to fill this gap, this paper compares incentive zakat agency mechanism between Indonesia and Malaysia.…”
Section: Introductionmentioning
confidence: 99%